2020
DOI: 10.1186/s42506-019-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Persian language health websites on Ebola disease: less credible than you think?

Abstract: Background: Ebola virus disease is an emergency situation in the area of international public health for which currently, there is no standard treatment. Thus, there is an essential need for awareness of individuals about the Ebola disease and consequently its prevention. Internet and health websites are considered a source of health information about certain diseases. Therefore, in this study, the credibility of Persian-language websites on Ebola is assessed. Materials and methods: The term "Ebola" was search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
(45 reference statements)
3
15
0
Order By: Relevance
“…The privacy policy is among seven core issues of website usability design and is of particular importance in creating effective websites [ 60 ]. Most websites assessed in this study had specified their privacy policy which is in line with the researches that have been carried out on other health topics [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The privacy policy is among seven core issues of website usability design and is of particular importance in creating effective websites [ 60 ]. Most websites assessed in this study had specified their privacy policy which is in line with the researches that have been carried out on other health topics [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, only 64.8% of the surveyed websites had specified the name and expertise of the authors (Table 2 ). In similar studies evaluating websites on MERS disease [ 45 ], and websites on Ebola disease [ 44 ], the authority was the least considered criterion [ 58 ], while patients need sufficient information about the author’s identity to be able to assess the trustworthiness of information [ 48 ]. Therefore, health websites on the most prevalent elderly diseases need to pay more attention to this criterion to increase their trustworthiness for their readers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HONcode is the oldest and most-used ethical and trustworthiness code for medical and health-related information available on the Internet [64]. It is reliable and has been used in multiple studies to assess the credibility of health websites [11,12,[14][15][16][65][66][67]. Therefore, we used the HONcode toolbar to identify certified websites containing information on COVID-19.…”
Section: Credibility Evaluation Toolmentioning
confidence: 99%
“…On March 13, 2020, Google Trends reported that the term "coronavirus" was searched five million times (supplemental appendix), underlining the importance of the Internet as a source for health information. However, multiple studies demonstrate that health websites may not be credible and may contain inaccurate or misleading information [11][12][13][14][15][16]. Therefore, the information found on health websites could increase uncertainty and anxiety and, thereby, serve to harm people's health [17][18][19].…”
Section: Introductionmentioning
confidence: 99%